THE INFLUENCE OF CONTENT MARKETING, BRAND AMBASSADORS, AND BRAND AWARENESS OF BUYING INTERESTS OF FASHION MATERNAL DISASTER BRAND CUSTOMERS - Baharudinsyah, Fuad Arsy; Putri, Kartika Anggraeni Sudiono (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This research focuses on the influence of Content Marketing, Brand Ambassador, and Brand Awareness marketing strategies on Buying Interests of Maternal Disaster fashion brand customers. The purpose of this study is to determine the effect of Content Marketing, Brand Ambassador, and Brand Awareness on Buying Interests of Maternal Disaster fashion brand customers either partially or simultaneously. This study uses a Quantitative Descriptive method. As for how to collect data using questionnaires distributed to respondents who meet the criteria. The sample used in this study was 124 respondents who were taken using the Maholtra formula with purposive sampling method. For data analysis using multiple linear regression analysis techniques and tested using the SPSS version 25 program.